2022
DOI: 10.1001/jamanetworkopen.2022.23821
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cerebrospinal Fluid Neurofilament Heavy Protein Levels With Clinical Progression in Patients With Parkinson Disease

Abstract: IMPORTANCENeurofilament light in biofluids has been associated with progression of Parkinson disease (PD), but the association between neurofilament heavy (NfH) and progression of PD has not been investigated. OBJECTIVE To evaluate the associations of cerebrospinal fluid (CSF) NfH (cNfH) levels and motor and cognitive progression in PD. DESIGN, SETTING, AND PARTICIPANTS This cohort study used data from the Parkinson Progression Marker Initiative ranging from June 2010 to November 2018. Participants were recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
(123 reference statements)
0
7
0
Order By: Relevance
“…Calcium and phosphorus disorders contribute to vascular calci cation. Previous research has revealed a favorable association between the degree of vascular calci cation and hyperphosphatemia, particularly in HD [25][26][27][28][29]. Nevertheless, several investigations have revealed no link between phosphorus and vascular calci cation in a metaanalysis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium and phosphorus disorders contribute to vascular calci cation. Previous research has revealed a favorable association between the degree of vascular calci cation and hyperphosphatemia, particularly in HD [25][26][27][28][29]. Nevertheless, several investigations have revealed no link between phosphorus and vascular calci cation in a metaanalysis [30].…”
Section: Discussionmentioning
confidence: 99%
“…The cytoskeleton of large projection neurons might be particularly prone to dysfunction, as suggested by the biochemical pathways of aggregation and displacement of axonal neurofilaments (Nf) proteins and the microtubule-associated protein tau, observed in motor neurons in ALS and pyramidal neurons in AD [ 184 ]. Moreover, axonopathy in cases of neurodegeneration, like AD [ 185 , 186 ], PD [ 187 , 188 ], and ALS [ 189 , 190 ], causes the release of phosphorylated neurofilament (pNf) into the cerebrospinal fluid (CSF), and subsequently into the blood. Thus, increased neurofilament light chain (NfL) in biofluids acts as a potential biomarker in NDDs like AD, PD, and ALS.…”
Section: Biochemical Pathways Involving Protein Homeostasis Autophagy...mentioning
confidence: 99%
“…In China, a significant increase in blood phenylalanine levels was found in some centers when their social medical insurance reimbursement policy for special foods was canceled; levels were lowered when the policy was restored. 1 In the US, no uniform reimbursement policy exists, and each state has different strategies regarding medical foods for IEM. A 2013 survey 4 asked parents questions regarding insurance coverage for medical foods and foods modified to be low in protein and found that even though most children had insurance coverage, more than 10% had uncovered expenses for medical foods and nearly 60% of families using modified low-protein food had minimal support for use of these products.…”
mentioning
confidence: 99%
“…5 Though new treatments for phenylketonuria have emerged, improving the likelihood of maintaining control of phenylalanine levels, the mainstay of treatment remains dietary restriction of phenylalanine. Wang et al 1 suggest that limiting access to medical foods results in diminished metabolic control of this condition. Our failure to assure access to these proven therapies limits the long-term potential for affected children and improving access may improve treatment efficacy.…”
mentioning
confidence: 99%
See 1 more Smart Citation